Temporally and Spatially Regulated Expression of the Linker Histone H1fx During Mouse Development. (September 2017) - Ichihara-Tanaka, Keiko; Kadomatsu, Kenji; Kishida, Satoshi
The linker histone H1fx is the least characterized member of the H1 family. To investigate the developmental changes of H1fx, we performed an immunohistochemical analysis of its expression pattern from embryos to adult mice. We found that H1fx was highly expressed during gastrulation, and was positive in all embryonic germ layers between E8.5 and E10.5, which mostly overlapped with the expression of the proliferation marker Ki-67. Neural and mesenchyme tissues strongly expressed H1fx at E10.5. H1fx expression began to be restricted at around E12.5. Western blot analysis of brain tissues demonstrated that the total expression level of H1fx gradually decreased with time from E12.5 to adulthood, whereas H1f0 was increased over this period. In adult mice, H1fx was restrictively expressed at the hypothalamus, subventricular zone, subgranular zone, medulla of the adrenal grand, islets of Langerhans, and myenteric plexus. Taken together, these data suggest that H1fx is preferentially expressed in immature embryonic cells and plays some roles in cells with neural properties.